Factors associated with treatment failure of patients with psychiatric diseases and injecting drug users in the treatment of genotype 2 or 3 hepatitis C chronic infection. - Alvarez-Uria, G; Day, J; Nasir, A; Russell, S; Vilar, F (2009)
BACKGROUND: Genotype 2/3 hepatitis C virus (HCV) has a good response to treatment with peginterferon and ribavirin. Patients with psychiatric disorders and injecting drug users (IDUs) are considered 'difficult to treat' and are often excluded from treatment despite the lack of evidence supporting this decision. AIMS: To investigate the outcome and factors associated with treatment failure in these groups. METHODS: This is an observational study of a cohort of patients infected by genotype 2/3 HCV. IDUs and patients with psychiatric diseases were not excluded from treatment. We performed an intention-to-treat analysis to evaluate factors related to treatment failure. RESULTS: A sustained virological response (SVR) was achieved in 91 of the 125 patients treated (72.8%). Patients with chronic psychotic disorders or former IDUs had SVR rates similar to other groups. After multivariate analysis, independent factors associated with treatment failure were liver cirrhosis [odds ratio (OR) 3.4, 95% confidence interval (CI) 1.1-10.4], a history of depression and not being on antidepressants at the commencement of HCV treatment (OR 4.4, 95% CI 1.2-16) and active IDUs (OR 7.3, 95% CI 1.77-30.4). CONCLUSIONS: Patients with a history of depression who were not receiving antidepressants and active IDUs are more likely to fail treatment for genotype 2/3 HCV and will need additional support.